Effect of probiotics on glycemic control and lipid profiles in patients with type 2 diabetes mellitus: a randomized, double blind, controlled trial - Peng, Xuchao; Xian, Hong; Ge, Ning; Hou, Lisha; Tang, Tianjiao; Xie, Dongmei; Gao, Langli; Yue, Jirong (Frontiers in Endocrinology, 2024)
This double-blind, placebo-controlled, randomized (1:1) clinical trial was conducted at the West China Hospital, Sichuan University, from March to September 2017. Eligible participants included adults aged 18 years and older, living in the community, diagnosed with type 2 Diabetes Mellitus according to ADA guidelines, capable of self-managing their diabetes, and able to visit the study site for follow-up. The intervention group received 25 ml of a probiotic beverage containing with over 10^8 CFU/mL of Lactobacillus, administered four times daily. An equal volume of inactivated Lactobacillus was administered to the control group and the control group was administered the same volume of inactivated Lactobacillus. This study aimed to evaluate the effectiveness of probiotics on glycemic control and other diabetes-related outcomes in patients with type 2 diabetes patients. The primary outcomes were changes in HbA1c and FBG levels post-intervention. Investigators, participants, and study site personnel were blinded to the treatment allocation until the conclusion of the study. Of the 490 participants screened, 213 were randomized to either the probiotics group (n = 103) or the placebo group (n = 110). After 16 weeks of follow-up, the probiotic group showed reductions in HbA1c [-0.18 (-0.70 to 0.18)] and FBG [-0.78 (-1.78 to 0.07)] post-intervention, similar to the placebo group with reductions in HbA1c [-0.20 (-0.63 to 0.10)] and FBG [-0.63 (-1.59 to 0.42)], but these changes were not statistically significant in PP and ITT analyses (P>0.05). Adverse events were similarly distributed among groups, indicating comparable safety profiles. This double-blind, randomized, placebo-controlled clinical trial was registered in the Chinese Clinical Trial Registry (ChiCTR-POR-17010850). Overall, 16-week probiotic supplementation showed no beneficial effects on glycemic control, lipid profiles, or weight.